Distúrbios da era informacional: conflitos entre a propriedade intelectual e a cultura livre - Almeida, Luis Eduardo Pinto Tavares de (2010)
This paper aims to examine the tensions arising from the transition from industrial capitalism to informational capitalism, especially those concerning the conditions of the possibilities offered by information technology, between the free flow of information and its blockade by the privatized capital. To this end, we focused on the institution of intellectual property that expresses the important features of this transition and around the major conflicts which occur. The work consists of literature review and empirical verification through experience of four listed. Thus we evaluate the transition process as irruptive possibilities of building a new economy, but constrained by conservative forces